Diversity of macrofungi in three land-cover types in Mandiangin Timur Village, Banjar Regency, South Kalimantan, Indonesia - INTAN AZZAHRA; MOCHAMAD ARIEF SOENDJOTO; ABDI FITHRIA; ARFA AGUSTINA REZEKIAH; MAULANA KHALID RIEFANI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Azzahra I, Soendjoto MA, Fithria A, Rezekiah AA, Riefani MK. 2026. Diversity of macrofungi in three land-cover types in Mandiangin Timur Village, Banjar Regency, South Kalimantan, Indonesia. Biodiversitas 27 (3): d270311. https://doi.org/10.13057/biodiv/d270311. Information on macrofungi across different land-cover types in rural areas, particularly in South Kalimantan Province, remains limited, although these organisms have potential applications in village development and community empowerment. This study aimed to record macrofungal species and their substrates in three land-cover types, namely dukuh (DU), agricultural land (AL), and shrubland (SL) in Mandiangin Timur Village, Banjar Regency, South Kalimantan, Indonesia; to compare fungal communities among these land-cover types; and to evaluate their utilization by the local community. Fungi and their substrates were surveyed along a 200 m × 3 m transect in each land-cover type as a baseline inventory. Supporting data included microenvironmental parameters such as soil pH, air temperature, air humidity, and light intensity, as well as information on mushroom utilization obtained through community interviews. A total of 52 macrofungal species representing 25 families were recorded. Of these, 47 species (25 families) were found in DU, 15 species (8 families) in AL, and 9 species (4 families) in SL. The Sørensen similarity index was highest between AL and SL (0.50), followed by DU and AL (0.35), and lowest between DU and SL (0.29). Each species was observed growing on a single substrate. Most species (63.46%) occurred on dead wood, while the remainder were found on soil, litter, and living wood. Bolbitius reticulatus was the only species recorded on the living stem of durian (Durio zibethinus). Of the total species documented, 20 were reported by the community as being utilized, and 18 of these were both reported and recorded during the village survey. Most of these species are used as food. Regular education and training programs are therefore recommended to enhance community knowledge, promote safe utilization, and support the conservation of macrofungi.